Implementation of The Window Shopping Model to Improve Fifth-Grade Students' Mathematics Learning Outcomes on Solid Geometry - Aini Chindy Afrita; Widia Sulistiani; Rahma Agustin; Ilham Arya Susanto; Aswasulasikin Aswasulasikin (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2026)
This classroom action research aimed to improve fifth-grade students' learning outcomes in mathematics, particularly on solid geometry, through the implementation of the Window Shopping cooperative learning model. The study was conducted in Class VB of SDN 02 Tanjung Batu during the 2024/2025 academic year with 20 students as participants. The research followed the Kemmis and McTaggart action research cycle, consisting of planning, action, observation, and reflection, and was implemented in two cycles. Data were collected using student activity observation sheets and learning outcome tests consisting of ten short-answer items administered during the pre-action stage and at the end of each cycle. The data were analyzed descriptively by calculating mean scores, mastery percentages, and observation percentages. The results showed that the mean score increased from 66.00 in the pre-action stage to 78.00 in Cycle I and 80.50 in Cycle II. The percentage of students achieving the minimum mastery criterion increased from 50% to 75% and then to 90%. Student activity also improved from 61.1% in Cycle I, categorized as sufficient, to 83.3% in Cycle II, categorized as good. These findings indicate that the Window Shopping model can improve students' learning outcomes and participation in learning solid geometry through collaborative discussion, peer tutoring, and gallery-based learning activities.